Real Challenges, Failed Changes: Attempts at Intercollegiate Cooperation within the History Students’ Scientific Movement in Poland during the Transformation Period, 1988–1999 - Budzyński, Piotr (1995– ) (Instytut Historii PAN, 2024)
The article examines the adaptive strategies undertaken by history students organised within student clubs during the period of transformation in Poland. The analysis considers both the opportunities and challenges that arose during this period and the specific actions students took to address these issues. Additionally, the author seeks to identify the underlying factors contributing to the limited success of these initiatives.
p. 191-211
Summary in English and Polish
Keywords: students; transformation; student scientific movement; 1990s; history students; International Students of History Association; student organisations